2007
DOI: 10.1021/jo701551f
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Synthesis of the Tricyclic Core of Martinellic Acid from 2-(Cyanomethyl)-3-oxo-N-arylbutanamides

Abstract: A SnCl4.5H2O-mediated facile and efficient one-step synthesis of the tricyclic core of martinellic acid from readily available 2-(cyanomethyl)-3-oxo-N-arylbutanamides was developed and a mechanism involving consecutive hydrolysis of a cyano group and a double annulation process is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
10

Relationship

8
2

Authors

Journals

citations
Cited by 47 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In the course of our continuous research on the direct syntheses of heterocyclic compounds from readily available acyclic precursors, we note that there is a potential vinylogous conjugated system in the Biginelli products (Schemes and ). We hypothesized that the Biginelli products 1 should form the vinylogous conjugated systems A in the presence of a suitable catalyst. Then, the vinylogous enolate A would attack aldehyde 2 to afford the intermediates B , subsequently leading to the products 3 via dehydration (Scheme ). In our efforts to develop highly efficient methods for functional group transformations, we found that iron salts are effective, reusable, operationally simple, and environmentally benign catalysts. As a result, we selected ethyl 6-methyl-2-oxo-4-phenyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate 1a (1.0 equiv) and 5-acetyl-6-methyl-4-phenyl-3,4-dihydropyrimidin-2(1 H )-one 1b (1.0 equiv), respectively, to react with 2a in the presence of FeCl 3 ·6H 2 O (10 mol %) in CH 3 CN at reflux (Scheme ).…”
mentioning
confidence: 99%
“…In the course of our continuous research on the direct syntheses of heterocyclic compounds from readily available acyclic precursors, we note that there is a potential vinylogous conjugated system in the Biginelli products (Schemes and ). We hypothesized that the Biginelli products 1 should form the vinylogous conjugated systems A in the presence of a suitable catalyst. Then, the vinylogous enolate A would attack aldehyde 2 to afford the intermediates B , subsequently leading to the products 3 via dehydration (Scheme ). In our efforts to develop highly efficient methods for functional group transformations, we found that iron salts are effective, reusable, operationally simple, and environmentally benign catalysts. As a result, we selected ethyl 6-methyl-2-oxo-4-phenyl-1,2,3,4-tetrahydropyrimidine-5-carboxylate 1a (1.0 equiv) and 5-acetyl-6-methyl-4-phenyl-3,4-dihydropyrimidin-2(1 H )-one 1b (1.0 equiv), respectively, to react with 2a in the presence of FeCl 3 ·6H 2 O (10 mol %) in CH 3 CN at reflux (Scheme ).…”
mentioning
confidence: 99%
“…On the basis of our studies on acetoacetamides in recent years, [41][42][43][44][45] we found α-fluorination of β-keto amides is a very important class of reaction. But the intolerable reaction mixture often is annoying to isolate.…”
Section: Resultsmentioning
confidence: 88%
“…During the course of our studies on the transformation of easily accessible acetoacetamide derivatives to highly functionalized N -containing heterocyclic compounds, we found substituted 2,3-dihydropyrroles can afford γ-amino ketones via a ring-opening reaction . We are also interested in the further functionalization of 2,3-dihydropyrroles, which can be readily prepared in high yield by the reaction of doubly activated cyclopropanes with amines .…”
Section: Resultsmentioning
confidence: 99%